Common variable immunodeficiency – case report (Journal of Health Sciences, 2013)
Common variable immunodeficiency (CVID) or acquired hypogammaglobulinemia is the type of primary immunodeficiency. Deregulation of the immune system, leading to hypogammaglobulinemia, defective activation and proliferation of T cells and dendritic cells, and malfunction of the cytokines are observed in CVID. The clinical picture of CVID varies, any organ or system can be affected, therefore the diagnosis is often difficult and delayed and sometimes is not always possible. This article describes a twelve years old boy with all the clinical signs of immunodeficiency, as confi rmed by laboratory. The main treatment consists of life-long immunoglobulin substitution in intravenous or subcutaneous form.